African cattle benefit from embryo transfer technology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The major protozoan diseases trypanosomiasis and theileriosis, cause heavy losses in African livestock. However, the practice of embryo transfer technology has been of increasing value in the production of genetically resistant stock. Using embryo...